ANALISIS KINERJA KEUANGAN DAERAH SEBELUM DAN SETELAH DITERAPKANNYA PP 06/2008 TENTANG PEDOMAN EVALUASI PENYELENGGARAAN PEMERINTAHAN DAERAH - , ANDRI SEPTIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to obtain empirical evidence regarding whether or not the existences of significant differences in the achievement of financial performance of local government before and after implementation of PP 6/2008 about the evaluation guidelines for local gorernance. This evaluation is a feedback on the performance of local government performance as well as the assessment and ranking close to the performance of local governments by using the measurement system and key performance indicators. The research data obtained from secondary data in the form of periodic budgeting and realization financial report (APBD). The research population are city/region in Jawa Tengah and Yogyakarta Province. The research sample randomly determined so that each member of the population has an equal chance to become a research sample. This research using Paired T-Test for the data obtained. The results showed the existences of the significant differences in the form of financial efficiency of public spending and the harmony of public spending. However, there was no difference in financial performance in the form of fiscal independence, the effectiveness of original region revenue (PAD), and original region revenue growth.